ANALISIS KASUS KORUPSI MENTERI PERTANIAN SYL DAN IMPLIKASINYA TERHADAP KONSEP PUBLIC TRUST DI INDONESIA - Andryana Perkasaputra; M. Rasikhan Wildan Mahdi; Rahmavenda Tri Puspitasari (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The corruption case involving the former Minister of Agriculture, Syahrul Yasin Limpo (SYL), has had a major impact on the concept of public trust in Indonesia. Law enforcement and transparency are considered important in maintaining public trust in the government and public institutions, so efforts to prevent corruption and enforce the law need to be increased to restore public trust and build clean governance. Optimizing supervision, developing an IT-based prevention system, making strict laws, and developing a complaint system that protects corruption whistleblowers are efforts to suppress cases of corruption that are rife in Indonesia. It is hoped that this essay can provide an in-depth understanding of corruption cases involving SYL and their implications for the concept of public trust in Indonesia, as well as contribute to efforts to prevent corruption, more effective law enforcement, and restore public trust in Indonesia.